EFFECTIVENESS OF THE BUDGET BY RESULTS UNDER THE MULTI-YEAR STRATEGIC PLANNING - Javier Melgarejo, Leoncio (2012)
With the globalization of the economic and financial world, and particulary with the subsequent free trade agreements with the United States, supported in the solvency of the liquidity, according to statistical manual of global public finance, has been imposed in our country, the financial currents. Meanwhile, since the beginning of the millennium has been implemented a new financial framework of the financial management structure of the Peruvian state that is standing on four strategic national systems. In this context: The new classifiers of budget, Plan of Accounts, Programming Multi-Year Public Investment “PMIP”, Programming the Annual Calendar “PCA” and performance budgeting (PPR), in contribution with fourth objective of the Strategic Plan 2009-2011 CEPLAN: “Articulation of the Plan with performance budgeting”, are given in order to achieve greater social benefit. Although, the National Strategic Plan called as PLAN BICENTENNIAL-PERU GO TO 2021, is still pending and not yet has been implemented the National Operational Plan, our country is still technically sailing without a compass. The implementation of performance budgeting, despite its low dynamics, and can be effective with multiyear projections of Public Investment and programmings of annual commitments financed even with heritage resources. The opportunity lies in business management.